Selective fetal reduction in complicated monochorionic twin pregnancies: A comparison of techniques. (30th September 2020) - Shinar, Shiri; Agrawal, Swati; El‐Chaâr, Darine; Abbasi, Nimrah; Beecroft, Robert; Kachura, John; Keunen, Johannes; Seaward, Gareth; Van Mieghem, Tim; Windrim, Rory; Ryan, Greg
Abstract: Objective: To compare perinatal outcomes associated with three methods of selective reduction in complicated monochorionic (MC) twin pregnancies: bipolar cord coagulation (BC), fetoscopic or ultrasound guided laser cord occlusion and radiofrequency ablation (RFA). Methods: Retrospective cohort study of complicated MC twin pregnancies undergoing selective fetal reduction at a tertiary fetal center over a 20‐year period. Obstetric and perinatal outcomes were compared. Results: 105 procedures met inclusion criteria: 74 RFAs, 17 lasers and 14 BCs. Procedure duration was significantly shorter for RFA (27.4 ± 15.8 minutes) compared to BC (91.7 ± 38.7 minutes) and laser (83.4 ± 40.4 minutes), P  < .0001). The incidence of preterm prelabor rupture of membranes (PPROM) and co‐twin demise did not differ between groups, however preterm delivery <34 weeks occurred less frequently following RFA (29.7%), compared to laser (64.7%) or BC (42.9%) ( P = .02); delivery <37 weeks was also less frequent following RFA (45.9%), compared to laser (76.5%) or BC (78.6%)( P = .01). The difference in preterm birth<34 weeks between RFA and laser was maintained after adjusting for cord occlusion indication and amnionicity (OR 3.96, 95% CI 1.27‐12.31). Conclusions: In our experience, RFA procedures were simpler, faster and associated with a lower risk of preterm delivery <34 and <37 weeks, compared to laser or BC.